Verbal to visual code switching improves working memory in older adults: an fMRI study - Osaka, Mariko; Otsuka, Yuki; Osaka, Naoyuki (Frontiers in Human Neuroscience, 2012)
The effect of verbal to visual code switching training on working memory performance was investigated in individuals aged 63 and older. During verbal working memory task performance, the training group (n = 25) was introduced to a verbal to visual code switching strategy while the control group (n = 25) was not exposed to such a strategy. Working memory recognition accuracy was enhanced only in the training group. To explore the neural substrates underlying these strategy effects, fMRI was used to measure brain activity in both groups during working memory task performance before and after an attention training period. In a comparison between pre- and post-training sessions, results showed increased activation in the anterior cingulate cortex (ACC). Relative to the control group, the post-training group exhibited increased activation in the left and right inferior parietal lobules (IPLs) and right superior parietal lobule (SPL). These findings suggest that use of a verbal to visual code switching strategy may assist older individuals in the maintenance of information in working memory.